EP.WE.843Acute Appendicitis Management During the COVID-19 Pandemic: A Prospective Cohort Study From A Large UK Centre. (28th October 2021) - Antakia, Ramez; XAnthis, Athanasios; Georgiades, Fanourios; Hudson, Victoria; Davies, Justin; Bennett, John
Abstract: Aims: The aim of this study was to determine the efficacy and outcomes of conservative versus surgical management of acute appendicitis (AA) during the pandemic. Methods: We conducted an observational study in a tertiary centre. Data was collected from all patients (≥16 years) with a diagnosis of AA between 1st November 2019 to 10 th March 2020 (pre-COVID period) and 10th March 2020 to 5th July 2020 (COVID period). Results: A total of 116 patients in the pre-COVID period were included versus 91 in the COVID period. 72.5% (n = 66) of the patients during the COVID period scored as high risk using the Alvarado score compared to 24.1% (n = 28) in the pre-COVID period (p-value<0.001). We observed a significant increase in radiological evaluation, 69.8% versus 87.5% of patients had a CT in the pre-COVID and COVID periods respectively (p-value=0.008). 94.9% of patients were managed operatively in the pre-COVID period compared to 60.4% in the COVID period (p-value<0.001). We observed more open appendicectomies (37.3% versus 0.9%; p-value<0.001) during the COVID period compared to pre-COVID period. More abscess formation and free fluid were found intraoperatively in the COVID period (p-value= 0.021 and 0.023 respectively). Re-attendance rate due to appendicitis-related issues was significantly higher in the COVID period (p = 0.027). Conclusions: Radiological diagnosis of AA was more frequent during COVID. More conservative management for AA was employed during COVID-19 pandemic, and for those managed operatively an open approach was preferred. Intra-operative findings were suggestive of delayed presentation during COVID without affecting the length of hospital stay.